Towards a gravity dual of the unitary Fermi gas - Bekaert, Xavier; Meunier, Elisa; Moroz, Sergej (Physical review. D, Particles, fields, gravitation, and cosmology, 2012)
Inspired by the method of null-dimensional reduction and by the holographic correspondence between Vasiliev’s higher-spin gravity and the critical O(N) model, a bulk dual of the unitary and the ideal nonrelativistic Fermi gases is proposed.